Religious Interpretation, Well Being, and Formation of Religious Attitudes On Covid-19 Survivors - Setiawan, Mohamad Nur Kholis; Muttaqin, Ahmad (Journal of Al-Tamaddun, 2022)
This article explains the attitude of social groups who have been declared exposed to the Covid-19 virus and are undergoing isolation facilitated by the government for 6-10 days until they are declared cured. Because they undergo quarantine with strict controls, they leave their main obligations as family breadwinners or professional workers. In a situation that is completely restricted, they have no alternative but to accept and undergo all procedures and stages of quarantine until they are completed. The article data comes from several Covid-19 patients participating in quarantine in Banyumas district in February 2022. Using a sociological approach and religious interpretation, the attitude of accepting the quarantine situation points to two things, first, religion is present in people who experience powerlessness as a result of the dysfunction of science and technology. Second, in this situation of powerlessness, religion is present to offer solutions that are beyond reality or transcendental. From these two situations, the social groups participating in the Covid-19 quarantine gave rise to religious attitudes which in the perspective of religious interpretation are understood as the practice of the teachings of gratitude, patience, trustworthiness, prayer, wisdom, and ihtiyar.